The reduction of Chrome in UG 2 flotation concentrate using hydrometallurgical means - Mokadze, Abel Monele (My University, 2022)
Flotation concentrates produced from processing UG-2 ore typically contain high Cr2O3 grades (>3 wt.%), which are not amenable to conventional PGM smelting processes. The solubility limit of Cr2O3 to deport to the silica glass phase is approximately 1.8 wt.% and below. Above this limit, the slag phase reaches saturation limits, which results in the formation of the infamous refractory Cr2O3 spinel phases. The overall net effect of high Cr2O3 in smelter operations includes, inter alia, increased furnace specific energy consumptions (kWh/t), the reduction of effective furnace capacity and poor PGM recovery. Existing interventions such as modification of slag chemistry by Cr2O3 dilution methods, redesign, and modification of existing physical and pyrometallurgical operations have not yielded any sustainable solutions. Thus, in this study, an acid leaching process using sulphuric acid was investigated to reduce Cr2O3 in UG-2 flotation concentrates. In the preliminary leaching experiments, exploratory batch leaching tests were conducted to study the leaching behaviour of Cr in UG-2 concentrate at different parameter levels of sulphuric acid concentration, leaching time and solid-to-liquid ratio. The experimental results showed that Cr extraction proportionally increased with the increase in sulphuric acid concentration and leaching time. On the contrary, Cr extraction increased with a decrease in solid-to-liquid ratio. Using a range of different solid-to-liquid ratios in the preliminary experiments, a 1:26 solid-to-liquid ratio gave a maximum Cr extraction of 87% at 75 %v/v acid concentration, 120°C temperature, 17 mL/min air flowrate and 5 hours leaching time. Using a fixed solid-to-liquid ratio of 1:3, at a temperature of 85°C, the Design of Experiments (DOE) was employed to establish optimum leaching conditions. From an industrial point of view, a 1:3 solid-to-liquid ratio and a temperature of 85°C were selected in alignment with the % solids that are generally required for minimum engineering design and practical operations, as well as the 85°C temperature for energy conservation. The DOE identified oxygen flowrate and acid concentration as significant process factors for Cr extraction. The interaction of temperature, leaching time and acid concentration was also found to be statistically significant. The response surface methodology (RSM), in conjunction with the central composite rotatable design (CCRD), established 45 v/v% sulphuric acid concentration, 15 mL/min pure oxygen flowrate and 3 hours reaction time as optimum leaching conditions. Using the optimised leaching conditions, further experiments conducted to test different solidto-liquid ratios yielded a Cr extraction of 7.6% at 1:2 solid-to-liquid ratio and 36.8% at 1:26 solid-to-liquid ratio. The 36.8% Cr extraction represents 1.33% reduction in Cr2O3 content from 3.63 wt.% to 2.3 wt.% in the UG-2 concentrate. The difference between the 87% Cr extraction obtained at 120°C and the 36.8% Cr extraction obtained at 85°C is attributed to the difference in the leaching temperature. Although the target for the solubility limit of Cr2O3 to deport in the silica glass phase was approximately 1.8 wt.% and below, the actual Cr2O3 content in the current smelter operations tends to fluctuate between 2 wt.% and 4 wt.%. Therefore, the Cr reduction from 3.63 wt.% to 2.3 wt.% achieved in the current study is considered to be within acceptable limits for PGM smelting processes. Thus, the reduced chrome content to 2.30 wt.% is a significant step towards achieving the 1.8 wt.% target.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2022